Greve no serviço público: uma análise a partir das greves ocorridas na secretaria de educação do município de Maracanaú no período de 2010 a 2022 - Montenegro, Maria Stella Monteiro (2024)
The present project entitled: “strike in the public service”, is the result of studies deve loped in the Professional Master's Degree in Public Policy Assessment (MAPP) at the Federal University of Ceará and its main objective is to evaluate the evolution of the right to strike within the socio-political context, economic, historical and legal, in order to justify the legislative delay in regulating a right enshrined in the Federal Constitution of 1988 as a rule of limited effectiveness - even without specific regulation - describing how strikes in the public service occur, such as strike movements within the scope of the Education Department of the Municipality of Maracanaú. Furthermore, analysis with qualitative aspects is used, without neglecting the quantitative aspects with an in depth approach, contextualizing the legality of the right to strike and this as a social phenomenon, briefly historicizing the wall movements in the world and in Brazil, as well as the problem of employment in Brazilian socioeconomic development, demonstrating the complex labor relations in the public sector and the challenges of union action – making an outline of strike movements within the scope of the Municipality of Maraca naú in the period between 2010 and 2022. It also demonstrates the position of the Judiciary regarding the legislative omission of Congress in regulating strikes in the pu blic service, in an attempt to demonstrate that the strike law, applied to the private sector, does not adapt to the legal regime of public servants